2014
DOI: 10.1021/jm5000563
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Systemically Active Metabotropic Glutamate Subtype-2 and -3 (mGlu2/3) Receptor Positive Allosteric Modulators (PAMs): Pharmacological Characterization and Assessment in a Rat Model of Cocaine Dependence

Abstract: As part of our ongoing small-molecule metabotropic glutamate (mGlu) receptor positive allosteric modulator (PAM) research, we performed structure–activity relationship (SAR) studies around a series of group II mGlu PAMs. Initial analogues exhibited weak activity as mGlu2 receptor PAMs and no activity at mGlu3. Compound optimization led to the identification of potent mGlu2/3 selective PAMs with no in vitro activity at mGlu1,4–8 or 45 other CNS receptors. In vitro pharmacological characterization of representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Recent studies have shown that mGluR2/3 positive allosteric positive modulators, which have enhanced receptor subtype selectivity, decrease cocaine intake in dependent animals (Dhanya et al, 2014). Using compounds with mGluR subtype selectivity is potentially useful as mGluR 2 and 3 show differential function and location.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that mGluR2/3 positive allosteric positive modulators, which have enhanced receptor subtype selectivity, decrease cocaine intake in dependent animals (Dhanya et al, 2014). Using compounds with mGluR subtype selectivity is potentially useful as mGluR 2 and 3 show differential function and location.…”
Section: Discussionmentioning
confidence: 99%
“…80,81 Briefly, cells were plated into 384-well, black-walled, clear-bottomed poly-D-lysine-coated plates at a density of 15,000 cells/20 µL/well in DMEM containing 10% dialyzed FBS, 20 mM HEPES, and 100 units/mL penicillin/streptomycin (assay media). Plated cells were incubated overnight at 37°C in the presence of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…One effort centered on the preparation and evaluation of a number of isoindolinone analogues such as 52 (Y = CH 2 ) and benzisothiazolone analogues such as 53 (Y = S). 266 Functional mGlu 2 activity, passive membrane permeability, rat plasma stability, and rat liver microsomal stability were assessed to evaluate the new compounds. Five optimized compounds were evaluated in rat PK studies, and all exhibited generally poor CNS penetration (brain/plasma K p ≤ 0.13); however, compound 52 was a low-clearance compound with good bioavailability and attained brain levels consistent with its mGlu 2 PAM functional potency following oral dosing.…”
Section: 2 Allosteric Modulators Of the Mglu2 And Mglu3 Receptorsmentioning
confidence: 99%